2017
DOI: 10.1093/ajcp/aqx071
|View full text |Cite
|
Sign up to set email alerts
|

CD200 Expression in Neuroendocrine Neoplasms

Abstract: ObjectivesCD200 expression has been well studied in hematopoietic malignancies; however, CD200 expression has not been well-characterized in neuroendocrine neoplasms. We examined CD200 expression in 391 neuroendocrine neoplasms from various anatomic sites.MethodsTissue blocks containing pulmonary small cell carcinoma, pulmonary carcinoid, large cell neuroendocrine carcinoma, pancreatic neuroendocrine tumor, gastrointestinal carcinoid, and Merkel cell carcinoma were evaluated for CD200 expression by immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…Analysis of previously published devil and DFT cell transcriptomes suggested that CD200 mRNA is highly expressed in DFT2 cells and peripheral nerves, moderately expressed in DFT1 cells, and lower in other healthy devil tissues (Figure 5A) 34, 35, 39 . As CD200 is an inhibitory molecule expressed on most human neuroendocrine neoplasms 40 , and both DFT1 and DFT2 originated from Schwann cells 35, 41 , we sought to investigate CD200 expression on DFT cells at the protein level. Staining of wild-type DFT1 and DFT2 cells with CD200R1-mOrange FAST protein showed minimal fluorescent signal (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of previously published devil and DFT cell transcriptomes suggested that CD200 mRNA is highly expressed in DFT2 cells and peripheral nerves, moderately expressed in DFT1 cells, and lower in other healthy devil tissues (Figure 5A) 34, 35, 39 . As CD200 is an inhibitory molecule expressed on most human neuroendocrine neoplasms 40 , and both DFT1 and DFT2 originated from Schwann cells 35, 41 , we sought to investigate CD200 expression on DFT cells at the protein level. Staining of wild-type DFT1 and DFT2 cells with CD200R1-mOrange FAST protein showed minimal fluorescent signal (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to high expression of CD200 on neuroendocrine neoplasms 40, 44 , CD200 is used as a diagnostic marker for several human blood cancers 4547 . DFT cells metastasize in the majority of cases 48 and our transcriptome results (Figure 5A) suggest that CD200 mRNA is more highly expressed in DFT cells than in peripheral blood mononuclear cells (PBMCs) 34, 35 .…”
Section: Resultsmentioning
confidence: 99%
“…The exact origin of Merkel cells remains controversial. It has been suggest that these cells originate from one of the neurocrest derivatives [ 39 , 40 , 41 ], keratinocytes, epidermal fibroblasts, early B cells or hair follicle stem cells [ 42 , 43 , 44 , 45 ].…”
Section: Merkel Cell Carcinomamentioning
confidence: 99%
“…These immunohistochemical markers are summarized in Table II. It is worth noting that ttf-1 is typically negative in mcc 12,20,21 . The pd-L1 marker was found to be expressed in 42% to 69% of cases of mcc.…”
Section: Diagnosis and Histologymentioning
confidence: 99%